Penatalaksanaan Fisioterapi Pada Cervical Root Syndrome Di Rsud Dr Hardjono S Ponorogo - Yuandita, Esta Anggela, Wahyuni, SSt. FT. M.Kes (2016)
Background: Pain in the neck is often called the root Cervical sydrome. Cervical root sydrome is a condition caused by irritation or cervical nerve root compression by discus protrusion intervetebralis. Cervical Root Syndrome is a collection of symptoms that interfere with the activity of the patient so that the appropriate treatment can be given can be handling non opratif and if a complaint is very heavy to do surgery to improved patient's condition. Objective: To determine the managemnt of transcutaneus electrical nerve stimulation (TENS) and exercise therapy can reduce pain in conditions Root Cervical Syndrome and determine the managemnt of transcutaneus electrical nerve stimulation (TENS) and exercise therapy can increase the area of motion, spasm of the neck and increase in functional activity of the neck disability indeks on condition Root Cervical Syndrome. Results : Reduction of motion pain becomes T1= 7 ,T6= 4,5 and tenderness T1= 4,5, T6=2 Increase LGS flexi T1=8, cm into T6=8 cm, the extension TI=6 cm into T6=7 cm, lateral right flexi T1=4cm be T6= 8 cm, lateral left flexi T1=5 cm be T6= 8 cm, right rotation T1= 10 cm be T6= 12 cm, left rotation T1= 10 cm be T6=13 cm and increase in functional activity of the neck disability indeks from T1= moderate limitations in your activity becomes T6 = limitations in activity was modest. Conclusion : Various problems that arise on condition of cervical root of the this syndrome are pain, limitation of LGS (range of motion) and spasm. Physiotherapy modalities are used to address the problem that TENS and exercise therapy. In addition patients were given education to do the exercise at home as it has been taught by the therapist. With the implementation modalities of therapy using the results obtained show a positive development which is evidenced by the decrease in pain (tenderness and pain motion) increase in LGS (range of motion), Neck muscle spasm and Increased functional activity. Keywords : Cervical Root Syndrome,Transcutaneus Electrical stimulation (TENS) and Exercise Therapy